Variasi dan Fungsi Tindak Tutur dalam Ceramah KH. Marzuki Mustamar (Kajian Pragmatik) - Moh. Iza Al Jufri; Wildana Wargadinata (Universitas Mulawarman, 2022)
This study describes the variations and functions of speech acts in KH's lectures. Marzuki Mustamar at the Isra' Mi'raj and Haul KH. Askandar in Banyuwangi on February 27, 2022. The descriptive qualitative method uses the theoretical basis of pragmatic speech acts. The study's results reveal the variations and functions of speech acts in KH. Marzuki Mustamar, among others, there are speech acts locutionary information and has an expressive meaning of humility, locutionary prohibition which has a prohibition function accompanied by humour, locutionary locutions that have a strong prohibition function, question locutions that have a function of attention, ask locutions that have the function of joking and humour, locutionary speech acts that function to state something, illocutionary speech acts of inviting which function as directives of invitation, speech acts of directive illocutionary requests/requests, speech acts directive illocutionary speech acts that have the function of praying, directive illocutionary speech acts that have the function of giving suggestions, directive illocutionary speech acts that function to give messages, expressive illocutionary speech acts that function as congratulatory, commissive illocutionary speech acts that function as threats and declaration illocutionary speech acts that function as a ban.